BIMBINGAN TEKNIS PENGUJIAN FORMALIN PADA MAKANAN UNTUK KERURAHAN POHJENTREK KOTA PASURUAN - achmad chumaidi; Yanty Maryanty; Dyah Ratna Wulan; Sabrina Adani Putri (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
PKM is carried out with the aim of mentoring in the form of education regarding the characteristics of formalin food and the impact of formalin on health, how to make your own formalin test kit.PKM is carried out in the form of guidance in the form of education regarding the characteristics of formalin food and the impact of formalin on health, how to make your own formalin test kit, and community training to identify formalin foods. This training was carried out by an online teleconference between the PkM implementing lecturers and the residents of Pohjentrek Pasuruan considering the COVID-19 pandemic was still ongoing, which was followed by the direct submission of modules related to the formalin test (containing information about the dangers of using formalin in food, how to make a formalin test kit and how to test formalin) and delivery formalin test kit solution.